Untersuchungen über Bionomie, Präimaginalstadien und Verbreitung der europäischen Sorhagenia-Arten (Lepidoptera: Walshiidae). - Malicky, Hans; Sobhian, Rouhollah (Contributions to Entomology = Beiträge zur Entomologie, 1971)
The bionomics of the european species of the genus Sorhagenia are described. The caterpillar of Sorhagenia lophyrella Douglas lives singly between spun leaves of Rhamnus cathartica and Rhamnus saxatilis, that of Sorhagenia rhamniella Zeller lives sociably between spun blossoms of Rhamnus cathartica, that of Sorphagenia janiszewskae Ridl mines in this years shoots of Rhamnus frangula and more rarely in other species of Rhamnus. Sorphagenia lophyrella and Sorhagenia rhamniella hibernate as eggs, Sorhagenia janiszewskae probably as imago in both sexes. On the basis of material from museums and private collections and from the author’s collections a survey is given of the distribution of the species. Caterpillar and pupa are described and illustrated, and distinctive characteristics of the caterpillars are mentioned.